Letter of condolence from Erika Krause to Max Bredig - Krause, Friedrich (1944)
Letter of condolence regarding the death of Georg Bredig (1868-1944) from Rike Krause to Max Albert Bredig (1902-1977). Rike is a German nickname for Erika.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Krause, Erika; Chemists; Condolence notes